Scanning laser fundus perimetry before laser photocoagulation of well defined choroidal neovascularisation - Rohrschneider, Klaus; Glück, Roland; Becker, Matthias D.; Holz, Frank G.; Kruse, Friedrich E.; Fendrich, Thomas; Völcker, Hans Eberhard (British journal of ophthalmology, 1997)
AIM To assess the centre of fixation before laser photocoagulation of well defined juxtafoveal or extrafoveal choroidal neovascularisation (CNV) secondary to age related macular degeneration (AMD), and to better predict visual function after treatment using scanning laser ophthalmoscope (SLO) fundus perimetry. - METHODS 19 consecutive eyes with juxtafoveal or extrafoveal CNV were examined by fundus perimetry before and after laser treatment with documentation of the fixation point using the SLO. The stability of fixation was defined as standard deviation around the mean fixation point. Overlays of fluorescein angiographic pictures and fundus perimetry were obtained using image analysis software. - RESULTS Fundus perimetry allowed accurate determination of the centre of fixation. Overlays demonstrated the precise geographic relation of the angiographically detectable foveal margin of the CNV and the centre of fixation. Thereby, prediction of the visual outcome with regard to reading ability was facilitated. Stability of fixation did not change significantly after treatment. - CONCLUSIONS Fundus perimetry using the SLO was helpful in patients who underwent laser treatment for juxtafoveal or extrafoveal CNV secondary to AMD and may aid the pretreatment counselling of such patients.